Individual Corporations in Indonesia: Fostering Economic Growth and Fairness through Simplified Business Formation: Perusahaan Perseorangan di Indonesia: Mendorong Pertumbuhan Ekonomi dan Keadilan melalui Penyederhanaan Pendirian Usaha - Faried, Femmy Silaswaty; Putri, Hanuring Ayu Ardhani; Arum, Dyah Ayu Sekar; Az-Zahra, Shaffanisa Alivia (Rechtsidee, 2023)
In the pursuit of an organized and conducive business environment, the Indonesian government has ratified the Job Creation Law, introducing a legal concept of Individual Corporations for small and medium-sized entrepreneurs (UMK). This normative study employs a conceptual approach through Economic Analysis of Law, using primary, secondary, and non-legal materials to analyze the implications and orientation of this policy. The research findings suggest that the implementation of Individual Corporations, requiring only one founder or shareholder for establishment, leads to ease in creation and expansion of micro-small businesses, potentially impacting the ease of doing business index positively. This policy also fosters a proportionately growing, fair national economic structure, and is expected to enhance employment opportunities. The introduction of Individual Corporations represents a significant change in Indonesia's corporate law, aligning with national goals to improve investment conditions.Highlights: Introduction of Individual Corporations requiring only one founder simplifies business formation. Positive impact on the ease of doing business index and alignment with national investment goals. Fosterment of a proportionate, growing, and fair economic structure, enhancing employment opportunities. Keywords: Individual Corporations, Economic Growth, Small Entrepreneurs, Business Formation